Dinamika Pemikiran Islam: Rekonstruksi Nilai Akidah, Syariah, dan Moral dalam Pendidikan Agama Islam - Reva Viramda Wulan; Ribbi Puspita Debi Sembiring2; Salsa Suci Yunda3; Siti Hafla; Uswatun Hasanah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This research aims to increase knowledge about Islamic studies and the field of Islamic studies, especially for students at the Syekh Abdul Halim Hasan Binjai Institute, especially in the Islamic Religious Education study program. The scope of Islam is broad and comprehensive which includes aqidah, sharia, morals and science. The field of Islamic studies also has various branches that focus on monotheism, fiqh, Sufism, kalam science, and Islamic history. The scope and development of Islamic studies proves to humanity that Islam is a teaching that can lead people to a better life, without having to disturb Islamic religious beliefs. The field of Islamic Religious Studies has finally received recognition, according toLIPI (Indonesian Institute of Sciences) at that time, Islamic Religious Science was a static and undeveloped science, from the past until now it has remained only the Al-Quran and Hadith. By studying the scope of Islamic studies based on aqidah, morals and Shari'a, we can produce a complete understanding of how individuals have faith, character, morals and obedience to the laws of Allah SWT.